Thorough QT/QTc in a Dish: An In Vitro Human Model That Accurately Predicts Clinical Concentration‐QTc Relationships. Issue 5 (2nd December 2018) - Blanchette, Alexander D.; Grimm, Fabian A.; Dalaijamts, Chimedullam; Hsieh, Nan‐Hung; Ferguson, Kyle; Luo, Yu‐Syuan; Rusyn, Ivan; Chiu, Weihsueh A.
Abstract : "Thorough QT/corrected QT (QTc)" (TQT) studies are cornerstones of clinical cardiovascular safety assessment. However, TQT studies are resource intensive, and preclinical models predictive of the threshold of regulatory concern are lacking. We hypothesized that an in vitro model using induced pluripotent stem cell (iPSC)‐derived cardiomyocytes from a diverse sample of human subjects can serve as a "TQT study in a dish." For 10 positive and 3 negative control drugs, in vitro concentration‐QTc, computed using a population Bayesian model, accurately predicted known in vivo concentration‐QTc. Moreover, predictions of the percent confidence that the regulatory threshold of 10 ms QTc prolongation would be breached were also consistent with in vivo evidence. This "TQT study in a dish, " consisting of a population‐based iPSC‐derived cardiomyocyte model and Bayesian concentration‐QTc modeling, has several advantages over existing in vitro platforms, including higher throughput, lower cost, and the ability to accurately predict the in vivo concentration range below the threshold of regulatory concern.